The study of seroprevalence of hepatitis E virus and an investigation into the lifestyle behaviours of the aborigines in Malaysia - Wong, Li Ping; Alias, Haridah; Choy, Seow Huey; Goh, Xiang Ting; Lee, Soo Ching; Lim, Yvonne Ai Lian; Kee, Boon Pin; Chua, Kek Heng; Kamarulzaman, Adeeba; Zheng, Zizheng; Zhao, Qinjian; Wu, Ting (Wiley, 2020)
Malaysia is a non-endemic country for hepatitis E virus (HEV) infection. However, seroprevalence as high as 50% among samples of aboriginal people were reported over two decades ago. A total of 207 samples collected from seven aboriginal villages in rural settlements across two states in Malaysia were analysed for anti-HEV IgG and IgM by an enzyme-linked immunoassay. Following the detection of anti-HEV seroprevalence, we organized health outreach to inform and educate the community. Qualitative interviews were conducted with individuals tested positive for anti-HEV antibodies. Data derived from interviews and observations were used to investigate possible lifestyle behaviours associated with HEV infection. Anti-HEV IgG was detected in six samples (5.9%) from the village of Dusun Kubur. Qualitative inquiry and observation study revealed poor dietary and household hygiene, contaminated food and water, contact with animal faeces, unsanitary and domestic waste disposal, and wildlife reservoirs could be the contributing factors for transmission and acquisition of HEV infection. Investigation during health outreach is important to provide insights for future empirical research and implementation for improvement of lifestyle behaviours among the aborigines. Managing the risk of HEV infection in the aborigines may reduce the risk of HEV transmission to the local communities. © 2020 Blackwell Verlag GmbH